Investigating the relationship between a sense of neighborhood belonging and social participation among Yazd residents: A cross-sectional study - Ameneh Marzban; Mohammad-Reza Rezaei; Nooshin Yoshany; Mahdiye Khaleghi Moori (Health Science Monitor)
Background & Aims: Social participation is a key strategy for promoting health and can greatly impact individual health outcomes. This study explores the relationship between the sense of neighborhood belonging and social participation among residents of Yazd city. Materials & Methods: A cross-sectional descriptive correlational study was conducted in 2023 among 20 to 70-year-old residents of Yazd neighborhoods. The sample size, based on statistical calculations, included 620 participants. Data were collected using a three-part questionnaire covering demographic characteristics, a standard sense of neighborhood belonging, and social participation. The data were analyzed using SPSS24, descriptive statistics, independent t-tests, ANOVA, and Pearson's correlation coefficient. Results: The mean and standard deviation of social participation scores were 85.36 ± 5.69, and the sense of neighborhood belonging was 31.15 ± 3.09. A significant relationship was found between social participation scores and gender. A positive, significant correlation existed between the seven components of neighborhood belonging and social participation levels. Among these, fulfillment of needs and loyalty showed the highest (r = 0.712, p = 0.00) and lowest (r = 0.416, p = 0.02) correlations with social participation, respectively. Conclusion:  The findings highlight a correlation between neighborhood belonging and social participation. To strengthen social networks and neighborhood identity, implementing educational programs, social and cultural activities, and creating safe public spaces are recommended. Building online and offline social networks, organizing sports and recreational activities, and developing charity initiatives can help reduce insecurity, increase residents' sense of responsibility, improve quality of life, and foster loyalty to the neighborhood, thereby positively influencing social participation.